Transparent Governance: Unveiling Accountability in Village Budget Management: Tata Kelola Pemerintahan yang Transparan: Mengungkap Akuntabilitas dalam Pengelolaan Anggaran Desa - Oktavia, Sofadiya; Biduri, Sarwenda (Universitas Muhammadiyah Sidoarjo, 2024)
This study investigates the accountability and transparency of village budget management practices through a qualitative interpretive approach. Focusing on a typical rural setting, the research aimed to measure the effectiveness of governance mechanisms that align with legal standards. Results reveal compliance with legal frameworks and proactive transparency demonstrated by public information boards detailing budget drafts. These findings highlight the effectiveness of transparent governance practices, suggesting their potential to enhance public engagement and trust in rural financial management. The study advocates for broader adoption of similar practices across various regions to improve local governance and accountability. Highlights : Legal Adherence: Demonstrates strict compliance with legal standards in the management of village budgets. Enhanced Transparency: Utilizes public information boards for budget drafts to ensure transparency and community involvement. Implementation Recommendation: Suggests the adoption of these governance practices in other villages to improve overall accountability and public trust. Keywords: Governance, Transparency, Accountability, Village Management, Public Engagement